A Textbook of Advanced Oral and Maxillofacial Surgery Volume 3 2016
DOI: 10.5772/63133
|View full text |Cite
|
Sign up to set email alerts
|

Applications of the Buccal Fat Pad in Oral and Maxillofacial Surgery

Abstract: The buccal fat pad "FP has become more and more popular in oral and maxillofacial surgery. Originally, it was described as an anatomic structure without any obvious function it was even considered to be a surgical nuisance. Nowadays, the most reported application of the "FP is the closure of oroantral communications. In this chapter, different aspects of the "FP such as its applications, anatomy, physiology, and complications are explained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 66 publications
(128 reference statements)
0
13
0
7
Order By: Relevance
“…The surface area which a BPF can cover is 10 cm 2 with a thickness of 6 mm and has an average volume of 10 cm 3 that's an average of 9.6 ml. 5 Syssacosis is a specialised type of fat with the following functions, protection of neurovascular bundles, preventing negative pressure while suckling in new born, separating masticator muscle from one and another and from the adjacent bone and thereby enhancing the inter muscular motion. 3 Buccal pad of fat is a versatile flap and most commonly it is used in reconstructive procedures such as reconstruction of oroantral fistula and closure of post excision defects and temporomandibular joints (TMJ) reconstruction, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface area which a BPF can cover is 10 cm 2 with a thickness of 6 mm and has an average volume of 10 cm 3 that's an average of 9.6 ml. 5 Syssacosis is a specialised type of fat with the following functions, protection of neurovascular bundles, preventing negative pressure while suckling in new born, separating masticator muscle from one and another and from the adjacent bone and thereby enhancing the inter muscular motion. 3 Buccal pad of fat is a versatile flap and most commonly it is used in reconstructive procedures such as reconstruction of oroantral fistula and closure of post excision defects and temporomandibular joints (TMJ) reconstruction, etc.…”
Section: Discussionmentioning
confidence: 99%
“…3 Buccal pad of fat is a versatile flap and most commonly it is used in reconstructive procedures such as reconstruction of oroantral fistula and closure of post excision defects and temporomandibular joints (TMJ) reconstruction, etc. 5 Ho published an article in 1989 on reconstruction and palatal and cheek defects with buccal pad of fat flap showed that the size of the defect is the main factor. Various studies show that a defect more the 4×4×3 cm in the maxilla are showing partial dehiscence due to lesser vascularity and due to the stretching of the flap.…”
Section: Discussionmentioning
confidence: 99%
“…The BFP also has rich vascular supply, with multiple tributaries from the maxillary, superficial temporal arteries and the facial artery. The excellent blood supply, proximity to potential defects, epithelialization outcome and successful outcomes make it a treatment of choice for oral reconstruction procedures (4). The BFP was first described (4,5) by Dr. Peter Egyedi in 1977 in a case series where the technique was successfully used in four patients who had large palatal defects.…”
Section: Discussionmentioning
confidence: 99%
“…The excellent blood supply, proximity to potential defects, epithelialization outcome and successful outcomes make it a treatment of choice for oral reconstruction procedures (4). The BFP was first described (4,5) by Dr. Peter Egyedi in 1977 in a case series where the technique was successfully used in four patients who had large palatal defects. Since then, its applications have broadened and the technique has been adopted to manage other oral and maxillofacial pathologies and oral reconstruction techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation